Effectiveness, implementation, and monitoring variables of intermittent hypoxic bicycle training in patients recovered from COVID-19: The AEROBICOVID study - Costa, Gabriel Peinado; Camacho-Cardenosa, Alba; Brazo-Sayavera, Javier; Viliod, Marcela Coffacci De Lima; Camacho-Cardenosa, Marta; Foresti, Yan Figueiredo; Carvalho, Carlos Dellavechia de; Merellano-Navarro, Eugenio; Papoti, Marcelo; Trapé, Átila Alexandre (Frontiers in Physiology, 2022)
Hypoxic exposure is safely associated with exercise for many pathological conditions, providing additional effects on health outcomes. COVID-19 is a new disease, then the physiological repercussions caused by exercise in affected patients and the safety of exposure to hypoxia in these conditions are still unknown. Due to the effects of the disease on the respiratory system, this study aimed to monitor 24 sessions of bicycle training performed under cyclic hypoxic conditions through analysis of peripheral oxygen saturation (SpO2), heart rate (HR), rate of perceived exertion (RPE) and blood lactate concentration ([La-]), in addition to monitoring possible acute responses to hypoxic exposure in patients recovered from COVID-19. Participants were allocated to three training groups: the normoxia group (GN) remained in normoxia for the entire session; the recovery hypoxia group (GHR) was exposed to hypoxia all the time except during the effort; the hypoxia group (GH) trained in hypoxia throughout the session. The altitude simulation showed effectiveness once the SpO2 mean was significantly different among the groups GN, GHR, and GH, being 96.9(1.6), 95.1(3.1), and 87.7(6.5), respectively. Besides, the hypoxia dose did not generate harmful effects since the most frequent Lake Louise score among groups was zero. The prescribed intensity and HR monitoring showed safety and effectiveness since participants maintained nearly 80% of sets at target, and the most frequent RPE was "3" (moderate). The training load (TRIMP) calculation, through HR and RPE, showed no significant difference between groups. The current strategy effectively promoted the altitude simulation and monitoring variables, being a safe exposure, as the low Lake Louise scores and the stable HR, SpO2, and RPE values showed during the sessions.